أثر الايمان الله في حياةالانسان في فكر الشيخ محمد الغزالي - نويوة, زهرة; حجاج, سميحة; برجوح, يسرى (جامعة الوادي university of eloued, 2020)
لقد حاولنا أن نتناول في هذه المذكرة آثار الإيمان بالله تعالى في حياة الإنسان، سواء من الناحية العلمية أو الفكرية أو الشخصية أو في جانب تعامل الفرد مع مجتمعه أو في سلوكياته وغيرها من الجوانب الأخرى، من خلال فكر الشيخ محمد الغزالي تحديدا. ولا يخفى أن لهذا الموضوع أهمية قصوى في الدراسات والأبحاث العقدية سواء من الناحية النظرية أو العملية. وقد وظفنا، من أجل تبيان هذا الموضوع، منهجا استق رائيا وصفيا تحليليا. وانتهينا إلى نتيجة حاسمة مفادها أن الإيمان بالله تعالى هو ملاذ الوجود الإنساني كله، والترياق لكل المآزق التي يمكن أن يتخبط فيها الإنسان. Abstract: In this research, we tried to take the consequences of human being's belief in God in his life, in scientific, thinking, personal or individual dealing with his society or behaviours or in other sides, according to mohammed el Gazzali thinking specifically. And this topic was very important in studies and streptococcus researches in both theoretical and applied sides. The analytical descriptive induction method was used to fulfil the work. To conclude, we achieved the decisive result provided that belief in God is a haven for all humans existence, and the antidote for the troubles that could human face.
ليسانس